2018
DOI: 10.1080/17518253.2018.1543456
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-mediated epoxidation of alkenes in supercritical carbon dioxide

Abstract: In this work, supercritical carbon dioxide was used as reaction media in the lipase-mediated epoxidation of alkenes for the first time. Under the optimal conditions (alkene (1 mmol), novozym 435 (15 mg), H 2 O 2 (50% aqueous solution, 1.4 mmol), n-caprylic acid (0.05 mmol), 40°C, scCO 2 (10 MPa, 25 mL)), high yields (83-98%) of epoxidation of alkenes could be obtained in a short reaction time. Furthermore, novozym 435 exhibited a satisfactory reusability in the epoxidations. Thus, this work not only presents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Zhang et al . used scCO 2 as a reaction medium in the epoxidation of alkenes mediated by lipase, and high yields of epoxidation were obtained . Furthermore, CO 2 can be used as a temporary protecting group for amines .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al . used scCO 2 as a reaction medium in the epoxidation of alkenes mediated by lipase, and high yields of epoxidation were obtained . Furthermore, CO 2 can be used as a temporary protecting group for amines .…”
Section: Introductionmentioning
confidence: 99%
“…29 Zhang et al used scCO 2 as a reaction medium in the epoxidation of alkenes mediated by lipase, and high yields of epoxidation were obtained. 30 Furthermore, CO 2 can be used as a temporary protecting group for amines. 31 A carbamic acid can be formed reversibly under CO 2 atmosphere, and this reaction is employed for the protection of the amine functionality in selective aza-Michael additions to methyl acrylate of a normally less reactive sulfonamide in the presence of a strong amine nucleophile, or of a cyclic secondary amine in the presence of an aliphatic primary amine, or of a -ketoester in the presence of amines.…”
Section: Introductionmentioning
confidence: 99%
“…Through the integration of multiple disciplines and technologies, researchers have been able to continuously explore and harness the power of enzymatic reactions in organic chemistry [20][21][22][23][24] .Enzyme catalytic promiscuity, which refers to the ability of catalyzing completely different types of reactions relative to the natural reaction, has been explored recently with the development of enzymology [25][26][27][28][29] . In this area, lipase is the widely used enzyme due to its broad specificity and excellent stability in various media [30][31][32][33][34][35][36] . As part of our ongoing research in developing new applications of lipase, we focused on the lipase-catalyzed synthesis of fluorene derivatives via benzannulation of indene dienes and benzoylacetonitrile (Scheme 1).…”
mentioning
confidence: 99%
“…[25][26][27][28][29] In this area, lipase is a widely used enzyme, due to its broad specificity and excellent stability in various media. [30][31][32][33][34][35][36] As part of our ongoing research in developing new applications of lipase, we focused on the lipasecatalyzed synthesis of fluorene derivatives through benzannulation of indene dienes and benzoylacetonitrile (Scheme 1). To the best of our knowledge, no example has been reported of a benzannulation of an indene diene and benzoylacetonitrile catalyzed by a biocatalyst.…”
mentioning
confidence: 99%
“…Recently, researchers have shown an increased level of interest in mining non-natural reactions of proteins, and many studies on this topic have been reported. Lipases and hemoglobins are ideal candidates because of their low cost, commercial availability, broad catalytic abilities, and good stability. Herein, we designed a novel lipase–hemoglobin cascade reaction for the efficient synthesis of quinoxalines via a three-component reaction of 1,3-dicarbonyl compounds, sulfonyl azides, and 1,2-diamines (Scheme ).…”
mentioning
confidence: 99%